The effect of meal replacements therapy on blood pressure and C-reactive protein: a systematic review and meta-analysis of randomized controlled trials - Fotros, Danial; Rohani, Pejman; Prabahar, Kousalya; Fatahi, Somaye; Sohouli, Mohammad Hassan; Guimarães, Nathalia Sernizon (Clinical hypertension, 2025)
Although some evidence shows the beneficial effects of meal replacement (MR) on blood pressure (BP) and inflammation as one of the main factors of cardiovascular disease, there are still no comprehensive findings in this field. Therefore, we investigate the effects of total and partial MRs on BP and C-reactive protein (CRP) in this comprehensive study and meta-analysis. In order to identify all randomized controlled trials that investigated the effects of MRs on BP and CRP levels, a systematic search was conducted in the original databases using predefined keywords. The pooled weighted mean difference (WMD) and 95% confidence intervals (CIs) were computed using the random-effects model. Forty studies were included in this article. The findings indicated significant reductions in systolic blood pressure (SBP) (WMD, -2.51 mmHg; 95% CI, -3.48 to -1.54; < 0.001), diastolic blood pressure (DBP) (WMD, -1.43 mmHg; 95% CI, -2.02 to -0.85; < 0.001), and CRP (WMD, -0.50 mg/L; 95% CI, -0.89 to -0.11; = 0.012) levels following MR consumption compared to the control group. The findings obtained from the subgroup analysis showed that MRs cause a greater reduction in SBP in people over 50 years of age, and the duration of the intervention ≤ 24 weeks. Also, the subgroup analysis shows the greater effect of DBP and CRP, respectively, in the type of intervention with total meal replacement and less equal to 50 years. In conclusion, it appears that MR, along with other lifestyle factors, can lead to significant improvements in BP and CRP.